Hepatic portoenterostomy for biliary atresia. A comparative study of histology and prognosis after surgery. Issue 6 (June 1981) - Lawrence, D; Howard, E R; Tzannatos, C; Mowat, A P
Abstract : Specimens of excised tissue from the porta hepatis in 26 infants with extrahepatic biliary atresia undergoing hepatic portoenterostomy were analysed histologically for the presence and size of biliary ductules. No correlation could be found between the establishment of effective biliary drainage and the number or size of biliary ductules. it is suggested that prognosis after surgery may be related to the intrahepatic lesion and age of the child at operation rather than to the histology of the extrahepatic bile duct remnants.